The Role of Women in Islamic Da'wah (Princess Study of Darus Salam Islamic Boarding School Girls' Alumni Perspective Torjun Sampang) - Abdullah Kafabi Hamda (Al-Amru: Jurnal Komunikasi dan Dakwah Islam, 2025)
Da'wah is an obligation for every Muslim, including women who play a crucial role in spreading religious knowledge, particularly in women's fiqh and community empowerment. The female alumni of Pondok Pesantren Darus Salam Torjun Sampang have significant potential in Islamic da'wah but face challenges such as economic limitations, pressure for early marriage, lack of family support, and limited access to higher education. This study focuses on the experiences and perspectives of alumni in da'wah while analyzing the opportunities and challenges they encounter. Using a qualitative approach and a case study method, data were obtained through in-depth interviews with six alumni informants to explore their experiences, motivations, and views on Islamic da'wah. The findings indicate that although women have great potential in da'wah, supported by pesantren education and motivation from their environment, they still face obstacles such as social stigma and time constraints. However, effective da'wah can be achieved through the principles of wisdom, compassion, and exemplary behavior in daily life. This study concludes that strong support from pesantren, families, and the community is essential in helping alumni overcome challenges and strengthen their role in da'wah to be more impactful and sustainable.